2011
DOI: 10.2174/092986711796150522
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Non-Receptor Tyrosine Kinase Fes in Cancer

Abstract: Non receptor protein tyrosine kinases are targets in the treatment of a number of diseases. This review focuses on the role of Fes tyrosine kinase and on the design of inhibitors of this protein. Fes and its homologously related protein Fer are the only two members of a distinct class of non receptor tyrosine kinases and they seem to play a role in cytoskeletal rearrangements and inside-out signaling associated with receptor-ligand, cell-matrix and cell-cell interactions. The knowledge of the three dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…For instance, mutations in ezrin within the conserved threonine residue prevent the formation of E-cadherinmediated cel-cell contacts during blastocyst formation in mice (Dard et al, 2001). It has been suggested that the small pool of ezrin that is present at cell-cell contacts is sufficient to recruit Fes kinase -a non-RTK that has also been implicated in cancer progression (Condorelli et al, 2011) -and to modulate junction formation by directly interacting with the SH2 domain of Fes kinase (Naba et al, 2008). This interaction is important for the localisation and activation of Fes, which consequently results in the disassembly of cell-cell contacts.…”
Section: Ezrinmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mutations in ezrin within the conserved threonine residue prevent the formation of E-cadherinmediated cel-cell contacts during blastocyst formation in mice (Dard et al, 2001). It has been suggested that the small pool of ezrin that is present at cell-cell contacts is sufficient to recruit Fes kinase -a non-RTK that has also been implicated in cancer progression (Condorelli et al, 2011) -and to modulate junction formation by directly interacting with the SH2 domain of Fes kinase (Naba et al, 2008). This interaction is important for the localisation and activation of Fes, which consequently results in the disassembly of cell-cell contacts.…”
Section: Ezrinmentioning
confidence: 99%
“…Furthermore, knockdown of radixin in PANC-1 cells resulted in an increase in E-cadherin expression, which is also seen in ezrindepleted cells . This implies that both ezrin and radixin may have an important role in the disruption of cell-cell contacts through the downregulation of E-cadherin and its relocalisation during cancer progression Condorelli et al, 2011;Li et al, 2012;Pujuguet et al, 2003).…”
Section: Radixinmentioning
confidence: 99%
“…PJA2 encodes an E3 ubiquitin‐protein ligase, and although the precise function of PJA2 has not been clarified, its expression level is moderately high in almost all normal tissues according to our present quantitative RT‐PCR results and microarray analysis (RefExA, http://www.lsbm.org/). FER is a 94‐kDa non‐receptor tyrosine kinase involved in the reorganization of the actin cytoskeleton or the modulation of cell–cell and cell–substrate interactions through its association with adhesion molecules and has been reported to play a role in the proliferation and growth of several cancers, such as prostate cancer, colon cancer, breast cancer, hepatocellular carcinoma, malignant mesothelioma, and gastric cancer . Especially, very recently, FER expression has been shown to be correlated with poor prognosis in NSCLC and renal cell carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…Activation of FES kinase requires active phosphorylation of Tyr713 located inside the activation loop and of Tyr 811. Hyperactivation of FES kinase is necessary for deregulated proliferation in human lymphoid malignancies, but aberrant activation is not associated with human tumors [17].…”
Section: Feline Sarcoma (Fes) Kinasesmentioning
confidence: 99%